Pancake kidney with single draining ureter: a rare developmental anomaly - Ahmad, Shabi; Mishra, Vikas; Mishra, Shirish (International Surgery Journal, 2020)
Pancake kidney is one of rare form of congenital developmental anomaly of kidney. Very rarely it is drained by a single ureter. We are reporting a case of pancake kidney with a single draining ureter. The diagnosis was made during the routine workup for abdominal pain and UTI in a 12 year old male child. Usually pancake kidney may be associated with other congenital malformation but in our case we did not find any. Pancake kidney is managed surgically as well as conservatively depending upon the presenting symptoms and problem. This case was managed conservatively for recurrent UTI.